Unique Signatures of Rashba Effect in Angle Resolved Magnetoresistance. Issue 1 (5th November 2021) - Gupta, Anshu; Kathyat, Deepak S.; Mukherjee, Arnob; Kumari, Anamika; Tomar, Ruchi; Singh, Yogesh; Kumar, Sanjeev; Chakraverty, Suvankar
Abstract: An unusual dependence of electrical resistance on the direction of the magnetic field, relative to that of current, in a 2D electron gas with strong spin‐orbit coupling formed at the LaVO3 –KTaO3 interface is reported. The observations are incompatible with any previously reported magneto‐transport measurements. Surprisingly, on the one hand the system exhibits signatures of chiral anomaly such as negative magnetoresistance and planar Hall effect, on the other hand, a number of features are even qualitatively beyond the existing theories. It is found that all the unusual features in transport are controlled by the quantum effects originating from strong spin‐orbit coupling induced spin‐momentum locking, and the traditional Lorentz mechanism plays a minimal role. The results not only open up a new avenue related to magneto‐transport in spin‐orbit coupled metals but also pave a path to engineer non‐magnetic materials as sensors for vector magnetic fields. Abstract : An unusual angular dependence of the magnetoresistance is observed for the conducting LaVO3 –KTaO3 interface. A negative‐magnetoresistance (NMR) is observed when the current ( I ) and magnetic field ( B ) are applied in the plane of the interface. For B < 7 T, largest NMR is observed when the angle between I and B is 90 o, for B > 7 T it occurs for 45 o .